Internalization of Honesty as a Christian Ethical Value among Christian Students - Kawatu, Lionel; Sumakul, Aprilia; Koda, Anjelina; Bawukes, Yehezkiel (Transpublika Publisher, 2025)
This research examines the internalization of honesty as a Christian ethical value among Christian students through a literature study approach. The phenomenon of declining academic integrity in higher education highlights an urgent need for character formation grounded in honesty values, particularly within Christian higher education contexts. The purpose of this research is to describe the concept of honesty in Christian ethics perspective, elaborate the process of honesty value internalization, and identify supporting and hindering factors. The method used is qualitative literature study with content analysis on academic sources from the 2020-2025 period. The study results show that honesty in Christian ethics is not merely moral behavior, but a reflection of character formed through relationship with Christ. The internalization process involves cognitive, affective, and behavioral stages that are strengthened by personal spirituality, contextual religious education, and supportive social environment. However, challenges such as normalization of academic cheating, achievement pressure, and digital culture become major obstacles. This research recommends an integrative model involving family, campus, church, and spiritual community in Christian student character formation. The implications of this research for higher education practice include developing integrative character education curriculum, strengthening lecturers’ role as moral mentors, forming a learning ecosystem that supports honesty value internalization, and multi-stakeholder collaboration in student character formation.